2016
DOI: 10.17265/2328-2150/2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Cytotoxic and Antioxidant Activities of Moroccan Pomegranate (Punica Granatum) with Phenolic and Flavonoid Contents

Abstract: Abstract:The Pomegranate (Punica Granatum), which belongs to the Lythraceae family, has been used for centuries in traditional Greco-Arab and Islamic medicine of its vermifuge properties and also to treat various diseases. The aim of this research was to investigate the cytotoxicity and antioxidant activities of Moroccan Pomegranate (peel, leaves, branches, flowers and corolla). Further, the biological activities were correlated with phytochemical contents of the plant extracts. Methanolic extract from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…The obtained results show a strong correlation coefficient between TPC and DPPH (r = 0.886), TPC and FRAP (r = 0.958) as well as DPPH and FRAP (r = 0.797; Table 4) which is in accordance with the previously published reports (Eddebbagh et al, 2016;Ozgen et al, 2008). …”
Section: Antioxidant Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results show a strong correlation coefficient between TPC and DPPH (r = 0.886), TPC and FRAP (r = 0.958) as well as DPPH and FRAP (r = 0.797; Table 4) which is in accordance with the previously published reports (Eddebbagh et al, 2016;Ozgen et al, 2008). …”
Section: Antioxidant Activitysupporting
confidence: 92%
“…Recently, the high antioxidant activity of the extracts from different parts of the pomegranate fruit such as the peel, juice and seeds have been reported (Shiban et al, 2012). Phenolic acids, anthocyanins and ascorbic acid, either alone or in combination, are responsible for the antioxidant activity of pomegranate (Eddebbagh et al, 2016). It has been shown that pomegranate juice contains the highest concentration of total polyphenols compared to other studied fruit juices (Vrhovsek et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results show a strong correlation coefficient between TPC and DPPH (r = 0.886), TPC and FRAP (r = 0.958) as well as DPPH and FRAP (r = 0.797; Table 4) which is in accordance with the previously published reports (Eddebbagh et al, 2016;Ozgen et al, 2008). Dżugan, M., Wesołowska, M., Zaguła, G., Puchalski, Cz.…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…The results showed that the greatest total flavonoid content was obtained in the methanolic extract. Eddebbagh et al (24) have found 221.70 mg QUE/ g dry weight in 80% methanolic extract and Abdolahi et al (16) have reported 64.38 ± 0.81 mg catechin equivalents per gram of dry weight in dried pomegranate flower. These differences might be related to solvent used and location.…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…The results showed that the highest total phenolic content was obtained in the methanolic extract, while the lowest was observed in the n-hexane extract. Eddebbagh et al (24) found that the phenolic content of 80% methanolic extract of dried pomegranate flower is 90.73 mg GAE/ g of dry weight flowers. Abdolahi et al (16) have found 28 mg GAE/ g dry weight in 70% ethanolic extract and Rashid and Shafi (25) have found 190.50 and 103.81 mg GAE/ g in methanolic and aqueous extracts in dried pomegranate flower.…”
Section: Total Phenolic Contentmentioning
confidence: 99%